2007
DOI: 10.1148/radiol.2421060083
|View full text |Cite
|
Sign up to set email alerts
|

x-Irradiation in Rat Liver: Consequent Upregulation of Hepcidin and Downregulation of Hemojuvelin and Ferroportin-1 Gene Expression

Abstract: x-Irradiation of the liver induced changes of hepcidin gene expression that are probably induced by acute phase mediators produced within the liver itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
50
2
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 46 publications
9
50
2
2
Order By: Relevance
“…These data confirm previous studies [35][36][37] in different rat models of liver injury, such as partial hepatectomy, CCl 4 administration, liver irradiation and turpentine oil-induced acute-phase response, that hepcidin-and Hjv-gene expression changes in the liver occur simultaneously and in an opposite direction. Specifically, when rats or mice are treated with GD intraperitoneally, hepcidin-gene expression is upregulated, whereas Hjv-and Fpn-1-gene expression are downregulated.…”
Section: Discussionsupporting
confidence: 91%
“…These data confirm previous studies [35][36][37] in different rat models of liver injury, such as partial hepatectomy, CCl 4 administration, liver irradiation and turpentine oil-induced acute-phase response, that hepcidin-and Hjv-gene expression changes in the liver occur simultaneously and in an opposite direction. Specifically, when rats or mice are treated with GD intraperitoneally, hepcidin-gene expression is upregulated, whereas Hjv-and Fpn-1-gene expression are downregulated.…”
Section: Discussionsupporting
confidence: 91%
“…47,48 In fact, the findings presented here are consistent with earlier studies obtained at RNA level, wherein a downregulation of Fpn-1-specific transcripts occurred in parallel with an increase in the level of the acute-phase cytokines (IL-6, IL-1b and TNF-a) reported in different rat models. [48][49][50] Furthermore, in our current study, treatment of rat hepatocytes with cytokines (IL-6, IL-1b and TNF-a) reduced the Fpn-1 gene expression; however, the impact of IL-6 was the strongest compared with that induced by the two other cytokines. Taken together, it became evident that early-observed hepatic Fpn-1 reduction could be due to direct effect of the acute-phase cytokines, 25,48 whereas late decrease in Fpn-1 protein could be due to the combination of both hepcidin and the acute-phase cytokines.…”
Section: Discussioncontrasting
confidence: 39%
“…In the sera of g-irradiated rats, significant upregulation of pro-Hepc serum level was associated with 30-fold upregulation of hepatic Hepc gene expression. 39 Similarly, the serum level of CINC-1 increased 15-fold, when the hepatic expression of CINC-1 was upregulated 260-fold during APR. 7 Also, the ELISA used to measure the serum Hepc concentration was not specific for biologically active Hepc-25.…”
Section: Discussionmentioning
confidence: 97%
“…7 This study underlines the Iron regulation during acute-phase reaction N Sheikh et al differences between the two animal models and indirectly confirms that IL-6 is the major player in modifying iron metabolism under acute-phase condition. 13,[38][39][40][41][42][43][44] Most studies to date have shown that the transcriptional changes in the Hepc gene expression parallel the changes in serum iron concentration; however, limited studies have been performed to show the changes in the concentration of this important hormone in the serum. [45][46][47][48] Intramuscular TO injection induced significant decrease of the serum iron concentration without a significant change in serum proHepc concentration.…”
Section: Discussionmentioning
confidence: 99%